difference between 12 and 3 ----> 12-3
Four times the difference --- 4(12-3)
divided by 6 ----> 4(12-3)/6
Can you calculate that?
(you said "the difference" , so it could have been 3-12 , but usually
in common language it would be the positive difference as I have shown)
Four times the difference between 12 and 3 divided by 6. What is the quotient?
11 answers
Four times the difference between 12 & 3 divided by 6
= (4 x (12-3))/6
= (4 x 9)/6
= 36/6
= 6
The quotient is 6.
= (4 x 9)/6
= 36/6
= 6
The quotient is 6.
Find the remainder when you subtract 40 from six times the sum of 7 and 5
Six times the sum of 7 and 5 is:
6 x (7 + 5) = 6 x 12 = 72
Now if you subtract 40 from 72:
72 - 40 = 32
So the remainder when you subtract 40 from six times the sum of 7 and 5 is 32.
6 x (7 + 5) = 6 x 12 = 72
Now if you subtract 40 from 72:
72 - 40 = 32
So the remainder when you subtract 40 from six times the sum of 7 and 5 is 32.
If the product of 16 and 4 is divided by the difference between 18 and 10 what is the quotient
The product of 16 and 4 is 16 x 4 = 64.
The difference between 18 and 10 is 18 - 10 = 8.
Therefore, if the product of 16 and 4 is divided by the difference between 18 and 10, the quotient is:
64 ÷ 8 = 8
The quotient is 8.
The difference between 18 and 10 is 18 - 10 = 8.
Therefore, if the product of 16 and 4 is divided by the difference between 18 and 10, the quotient is:
64 ÷ 8 = 8
The quotient is 8.
When 6 is subtract from the product of 3 and the quotient of 27 divided by 9 what will be the remainder
The quotient of 27 divided by 9 is equal to 3.
So, the product of 3 and the quotient of 27 divided by 9 is:
3 x 3 = 9
If 6 is subtracted from 9, we get:
9 - 6 = 3
Therefore, the remainder is 3 when 6 is subtracted from the product of 3 and the quotient of 27 divided by 9.
So, the product of 3 and the quotient of 27 divided by 9 is:
3 x 3 = 9
If 6 is subtracted from 9, we get:
9 - 6 = 3
Therefore, the remainder is 3 when 6 is subtracted from the product of 3 and the quotient of 27 divided by 9.
What is the sum of 6 and the quotient of 35 divided by 7
The quotient of 35 divided by 7 is 5, since 7 times 5 is 35.
So, the sum of 6 and the quotient of 35 divided by 7 is:
6 + 5 = 11
Therefore, the sum of 6 and the quotient of 35 divided by 7 is 11.
So, the sum of 6 and the quotient of 35 divided by 7 is:
6 + 5 = 11
Therefore, the sum of 6 and the quotient of 35 divided by 7 is 11.